Cervical Computed Tomography Angiography Rarely Leads to Intervention in Patients With Cervical Spine Fractures. Issue 8 (December 2020) - Dunn, Conor John; Changoor, Stuart; Issa, Kimona; Moore, Jeffrey; Moontasri, Nancy J.; Faloon, Michael Joseph; Sinha, Kumar; Hwang, Ki Soo; Ruoff, Mark; Emami, Arash
Study Design: Retrospective cohort study. Objectives: To evaluate the impact of computed tomography angiography (CTA) in the management of trauma patients with cervical spine fractures by identifying high-risk patients for vertebral artery injury (VAI), and evaluating how frequently patients undergo subsequent surgical/procedural intervention as a result of these findings. Methods: All trauma patients with cervical spine fractures who underwent CTA of the head and neck at our institution between January 2013 and October 2017 were identified. Patients were indicated for CTA according to our institutional protocol based on the modified Denver criteria, and included patients with cervical fractures on scout CT. Those with positive VAI were noted, along with their fracture location, and presence or absence of neurological deficit on physical examination. Statistical analysis was performed and odds ratios were calculated comparing the relationship of cervical spine fracture with presence of VAI. Results: A total of 144 patients were included in our study. Of those, 25 patients (17.4%) were found to have VAI. Two patients (1.4%) with VAI underwent subsequent surgical/procedural intervention. Of the 25 cervical fractures with a VAI, 20 (80%), were found to involve the upper cervical region (4.2 OR, 95% CI 1.5-12.0; P = .007). Of the 25 who had a VAI, 9 were unable to undergo reliable neurologic examination. Of the remaining 16 patients, 5 (31.3%) had motor or sensory deficits localized to the side of the VAI, with no other attributable etiology. Conclusions: Cervical spine fractures located in the region of the C1-C3 vertebrae were more likely to have an associated VAI on CTA. VAI should also be considered in cervical trauma patients who present with neurological deficits not clearly explained by other pathology. Despite a finding of VAI, patients rarely underwent subsequent surgical or procedural intervention.